LACTIC ACID BACTERIA ISOLATE 18A PHENOTYPIC IDENTIFICATION - Suardana, I Wayan; Sukoco, Hendro; Antara, Nyoman Semadi (Buletin Veteriner Udayana; Vol. 10 No. 1 Pebruari 2018DO - 10.24843/bulvet.2018.v10.i01.p01, 2018)
Lactic Acid Bacteria (LAB) is a bacterium that has an ability to inhibit a pathogenic bacteria growth, including isolates 18A. The aim of this study is to determine the species of LAB isolates 18A by conventional tests and API 50 CH test. This study was a descriptive observational study, with lactic acid bacteria isolates 18A were obtained from bali cattle’s colon as an object. LAB isolates 18A were re-cultured on MRS media, catalase test, and Gram staining. Identification test were performed by CO2 production test, growth in the presence of 15% NaCl, growth at 10°C, and growth at pH 9.6. Confirmation test were performed using API 50 CH (Standard Analytical Profile Index). The results indicated that LAB isolate 18A were able to grow well on MRS broth media, catalase-negative, Gram-positive, and spherical-chain in shape. Identification test revealed that the bacteria is homofermentative, were able to grow at 10°C, and do not grow at pH 9.6. Fermentation test using API 50 CH showed that LAB isolates 18A were able to degrade 15 sugar components, consist of no: 5, 10, 11, 12, 13, 22, 24, 25, 26, 27, 28, 29, 30 , 31, and 39. Based on conventional identification results, it can be concluded that BAL isolates 18A is a Lactococcus. In addition, the result of API 50 CHL test showed that BAL isolates 18A is a Lactococcus lactis ssp lactis 1 .